Perceived employability and ability self among Finnish university students - Hannu Räty; Ulla Hytti; Kati Kasanen; Katri Komulainen; Päivi Siivonen; Inna Kozlinska (Springer, 2022)
Employability is an increasing concern for university students. Our survey set out to examine university students’ perceptions of their employability and the ways in which these perceptions relate to positions that subsequently connect students to working life: students’ self-representational position or “ability self”, and students’ life-historical positions such as chosen field of study, phase of degree and working life experience. The participants comprised a sample of students (N = 1819) from two Finnish universities, representing diverse fields of study. It was found that apart from the field of study, the perceived proximity to graduation and working life was associated with the perception of employability. Furthermore, a set of self-attributed capabilities was associated with students’ perceptions of employability, particularly extroversion, ambitious competitiveness, mental strength and the desired characteristics of a good employee; however, the attribution of academic skills showed opposing effects. It was concluded that both self-representational and live-historical positions are part of the construction of students’ optimism regarding their employability.